Website development for Grace Baptist Church - Jiang, Dayou (Kansas State University, 2013)
Grace Baptist church is a Christian church that is actively reaching out to college students, military families and other groups of people. They aim to impact not only the community of Manhattan and nearby areas but also to reach around the world with the Gospel. It is very important for the church to have a user friendly website so as to introduce Grace Baptist Church to people who may have an interest in Christianity and church activities. Considering the limitations of the current church website, the administrator of Grace Baptist Church decided to have a new website that better represents the church and attract people to know more about the church’s mission. I and another student Nikhita Addanki from computer science department were working together on this project. The main objective of this project is to redesign and implement a website for Grace Baptist Church. The website will be used to post updated information about church events, announcements and opportunities, share videos and blogs, and let people around the world know about Grace Baptist Church and its mission. The new website has a better page appearance, a well organized structure and mobile support. It is implemented using WordPress, a free content management system, so that people from the church can early update the information without knowing much about web techniques. Alone with the implementation, I also reviewed some articles regarding website usability and performance to assure the quality of the new website. A performance test has also been conducted to evaluate the result.
Keywords: Website development; Computer Science (0984)